Enhancing the Preoperative Experience and Satisfaction of Surgical Patients at an Academic Medical Center through Implementation of a Smartphone Application. Issue 11 (November 2019) - Ramakrishnan, Divya; Garson, Les; Mensah, Paulette; De Los Santos, Joe; Elfenbein, Dawn M.
Preoperative education improves patient satisfaction and postsurgical outcomes, but the use of mobile applications to provide preoperative education in a large population has not been extensively studied. The objective of this study was to determine whether patient use of a text messaging application would lead to a high patient satisfaction rating. Patients undergoing general surgical procedures at our institution were invited to use the application. Each patient received educational messages and was sent a feedback survey postoperatively. Seven hundred twenty-three patients were invited to register with the application, and 402 patients (56%) did so. One hundred sixty-eight (42%) patients who registered filled out the postoperative survey. Of the surveyed patients, 94 per cent stated that they used smart phones daily or a few times a week. The use of the application in our patient population led to good or excellent patient satisfaction scores. Further investigations to determine whether this technology reduces postoperative visits or improves outcomes are ongoing.